Progress accomplished since the International Conference on Population and Development: A perspective of non-governmental organizations - Raj Abdul Karim (Asia-Pacific Population Journal, 2009)
Family planning, today encompassed in the context of comprehensive sexual and reproductive health and reproductive rights, has historically always been an area of strength of non-governmental organizations (NGOs), civil society groups and individuals. From the dawn of the twentieth century, a few “Brave and Angry” women and men activists advocated for women to be able to exercise birth control and the right to voluntary motherhood. They saw the physical, emotional and financial burdens women bore and understood their longing to limit the size of their families and the risks they took to do so. Those women took it upon themselves to share information with other women and distribute “home made” contraceptives even though it put their lives at risk for contravening their government’s policies or legislation. Yet they pursued their firm beliefs and their names continue to command respect and provide never-ending motivation and determination to the Margaret Sangers of today.